Traumatismo craneoencefalico moderado - Acosta López, María de Lourdes (2018)
Are alterations that cause damage to the brain that are generated by blows against objects that many of the cases fail to break the skin, this will cause a deficit in consciousness, cognitive, perceptual malfunction and daily activities such as talking and walking. Among the neurological diseases, the traumatic brain injury is located in the highest range because they occur with more continuity as in severity. classification: According to the integrity of the cranial covers: closed, open, mild, moderate and severe. PUPILS: within the physical examination pupil measurement is also performed, the standard is 2 to 5 millimeters, this assessment is characterized by the reactivity or response to reflexes before stimuli with light, the alterations are: the mydriasis that is the upper pupil of 5 millimeters, the miosis is the opposite of mydriasis is presented by the lower measurement of 2 millimeters and finally the anisocoria which is the asymmetry of several pupils. To develop the process of nursing care in a patient of 21 years of age with a diagnosis of moderate head trauma. that contribute to the solution of decrease of health problems detected. Execute the planned nursing activities.